Rancang Bangun Sistem Monitoring Kualitas Air Berbasis IoT dengan Fitur Pengurasan Air Otomatis untuk Budidaya Lobster Air Tawar - Ramadhan, Muhammad Rizky; Nurussa’adah, n/a; Abidin, Zainul (Jurnal Mahasiswa TEUB, 2025)
This research discusses the design and implementation of an IoT-based water quality monitoring system with automatic drainage features for optimizing freshwater crayfish aquaculture. The system utilizes ammonia (MQ-135), turbidity (SEN0189), temperature (DS18B20), and pH (pH-4502C) sensors to monitor water quality parameters in real-time. Sensor data is transmitted through ESP32 to the Blynk IoT platform for remote monitoring. The system is equipped with an automatic water drainage feature that activates when water parameters exceed predetermined thresholds. Test results show that the system can detect water parameters with high accuracy: ammonia sensor 82,42%, turbidity sensor 91,39%, temperature sensor 98,87%, and pH sensor 98,48%. The system successfully maintains water parameters within ideal ranges: ammonia <0.05 mg/L, turbidity <25 NTU, temperature 24-28°C, and pH 7.0-8.5. The system also successfully provides real-time notifications and activates automatic drainage when needed. The implementation of this system can improve aquaculture management efficiency and freshwater crayfish health.Keywords: IoT, Water Quality Monitoring, Crayfish Aquaculture, Ammonia Sensor, Turbidity Sensor, Automatic Drainage